IDENTIFIKASI MOLEKULER BEAN COMMON MOSAIC VIRUS YANG BERASOSIASI DENGAN PENYAKIT MOSAIK KUNING KACANG PANJANG - Melinda .; Tri Asmira Damayanti; Sri Hendrastuti Hidayat (Universitas Lampung, 2015)
Molecular identification of bean common mosaic virus associated with yellow mosaic disease on yard long bean. Bean common mosaic virus (BCMV) has been reported as one of the causal agents of yellow mosaic disease on yard long bean in West Java and Central Java. Infected plants showed mosaic, yellowing, and mixture of yellow mosaic. The research was conducted to identify the diversity of BCMV associated with yellow mosaic disease based on coat protein (CP) gene sequences. Symptomatic leaf samples were collected from yard long bean growing areas in several districts in West Java (Bogor, Cirebon, Subang, and Indramayu), and several districts in Central Java (Tegal, Klaten, Solo, Yogjakarta, Sleman, and Magelang). Molecular detection using RT-PCR method was carried out by using specific primer to BCMV which will amplify the CP gene. DNA fragment, + 860 bp in size, was successfully amplified from 8 out of 13 leaf samples, i.e samples from three villages in Bogor District (Cangkurawok, Bubulak, Bojong), and five samples from District of Cirebon, Subang, Solo, Sleman, and Tegal. Sequence analysis of those DNA fragment showed that 4 isolates (Bogor-Cangkurawok, Subang, Solo and Sleman) had the highest homology to BCMV-BlC from Taiwan, whereas 2 isolates (Cirebon and Tegal) had the highest homology to BCMVNL1 from England. Further, phyllogenetic analysis revealed that those of 4 isolates were closely related to BCMV-BlC from Taiwan based on nucleotide as well as amino acid sequences; while those other 2 isolates were closely related to BCMV-NL1 from England based on nucleotide sequences but closely related to BCMV-BlC Y from China based on amino acid sequences. Phyllogenetic analysis showed that those of 6 BCMV isolates separated in two different clusters; 4 isolates (Bogor- Cangkurawok, Subang, Solo, and Sleman) in cluster 1 together with BCMV-BlC from Taiwan, while other 2 isolates (Cirebon and Tegal) in cluster 2 together with BCMV-NL1.